SAT0359 Rheumatologists underestimate daily calcium intake in patients with osteoporosis. (23rd January 2014) - Rasch, L.; van Bokhorst-de van der Schueren, M.; van Tuyl, L.; Bultink, I.; Lems, W.
Abstract : Background: Calcium supplements are widely used for the prevention and treatment of osteoporosis. However, in recent literature there is a controversy whether or not excessive calcium supplementation may be associated with increased risk of cardiovascular events (1-2). In daily practice, rheumatologists at the VUmc use a short calcium list to estimate the dietary intake of calcium, which is the basis for the prescribed amount of calcium supplementation. An accurate estimation is important to be able to prescribe the adequate amount of calcium supplementation to reach the recommended levels of 1000-1200 mg of calcium per day, without a possible increase of the risk of cardiovascular events. Objectives: Validation of a short calcium intake list used by rheumatologists with a detailed dietary history (DH), assessed by a dietician, as the reference method. Methods: This cross-sectional study included patients attending the outpatient department of rheumatology at the VUmc for the treatment of primary or secondary osteoporosis. For participating in this study, subjects had to be diagnosed with and treated for osteoporosis, based on a low T-score in hip and/or lumbar spine, with or without a vertebral fracture. In addition, subjects in the group of secondary osteoporosis had to be diagnosed with a rheumatic disorder. The short calcium list calculated calcium intake by asking for the amount of portions of milk, yoghurt (multiplied by 180 mg of calcium per portion), and cheese (multiplied by 155 mg of calcium per portion). In addition, 250 mg of calcium from other products was added. This short list was compared with a DH with specific focus on calcium products and extra attention for portion sizes of dairy products and cheese. On forehand, a difference of at least 250 mg of calcium between both methods was formulated as clinically relevant. Results: Sixty-six subjects (31 with primary osteoporosis and 35 with secondary osteoporosis) were included. The mean nutritional calcium intake measured via the short calcium list (825±259 mg) was lower than via the DH (1113±424 mg) (p<0.001). Furthermore, the mean difference between both methods was 289±346 mg of calcium: in 37 of the 66 patients (56.1%) the short calcium list scored more than 250 mg lower than the DH, and in only 4 of the 66 patients (6.1%) the short calcium list scored more than 250 mg higher than the DH. In total, 55 patients (83.3%) reached an overall intake higher than the upper limit of the recommendation of 1200 mg of calcium per day. Conclusions: The short calcium list gives a substantial and clinically relevant underestimation of dietary calcium intake in more than 55% of the patients. Therefore, the short calcium list is not a valid method to measure calcium intake of patients with osteoporosis. This is a clinically relevant finding because of the rumour around an increased risk of cardiovascular events associated with a too high overall calcium intake. References: Bolland MJ, et al. BMJ 2008 Feb 2;336(7638):262-6. Lewis JR, et al. J Bone Miner Res 2011 Jan;26(1):35-41. Disclosure of Interest: None Declared